Skills for Competitiveness : Leveraging Skills for Competitiveness in Europe - World Bank (World Bank, Washington, DC, 2018)
The global technology and innovation frontier pushes forward at a rapid pace, and countries around the world seek to either keep up, or catch up. Countries at the frontier are forward-looking, have robust economies, are open to investment and technology, and have competitive, well-matched workforces. And countries that want frontier-combatible workforces require agile, demand-driven training arrangements that allow for swift entry and re-entry to training. After all, as the fourth industrial revolution unfolds, technology and markets continue to change at ever-increasing speeds. Training systems must adapt to an environment in which skills need frequent updating, and find ways to leverage employers’ comparative advance in providing that training. This technical note seeks to help the public and private sectors understand what is currently being done to help achieve workforce skills convergence, and to begin thinking about how they might employ public-private arrangements to incentivize training at firms of all sizes. It offers a fresh take on the lifelong learning model and presents a framework for precision training, a demand-driven approach to training that offers workers opportunities to upgrade their skills exactly when, where, and how they need to. In Europe, this perspective may be particularly useful for countries with lagging regions that struggle with low incomes, low growth, and low skills (such as Romania and Poland). However, this technical note is designed to be applicable to all countries, including their policymakers, private employers, and training institutions. Even high-income countries with cutting-edge training policies, such as Germany and the United Kingdom, have regions that struggle economically and educationally. Precision training provides a valuable tool for skills development challenges in these contexts, too.